Study of the Contagion Mechanism for Opening Risk of Emerging Equity Markets in BRICS Countries: A Pitch - Rui Xue (Journal of Accounting and Management Information Systems (JAMIS), 2016)
This pitch letter outlines the application of Faff's (2015a) 2-page pitching template to my completed paper "Study on the Contagion Mechanism of Opening Risk and Emerging Equity Markets in BRICS Countries" and my personal reflection on the pitching exercise. Pitching research is shown to be a powerful tool for researchers and of great help to my current and future research work.
Keywords: G10; 650; Pitching Research; Contagion Mechanism; Opening Risk; BRICS